A feasibility study of a tailored mindfulness-based group intervention for psychological distress and adjustment for allogeneic hematopoietic stem cell transplant outpatients - Litza Kiropoulos; Phuong Linh Dang; Vanja Rozenblat (BMC Cancer)
Abstract Background Mindfulness-based interventions have provided consistent benefits for the physical and emotional wellbeing of cancer patients. However, their feasibility has not been examined in patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT), particularly in the post-transplant phase. The aim of this study was to examine the feasibility and acceptability of a six-week group-based mindfulness intervention and to examine whether this intervention improves psychological adjustment to cancer in haematological cancer patients who have undergone an allogeneic HSCT. Methods Twenty eligible participants were recruited from the Haematology and Bone Marrow Transplant Unit at the Royal Melbourne Hospital, Melbourne, Victoria. Primary outcomes were the feasibility and acceptability of the mindfulness intervention. Secondary outcomes include examination of depression, anxiety, quality of life, psychological adjustment to cancer, mindfulness skills, emotion regulation strategies, and cancer-related pain, fatigue, and physical functioning. Evaluation of treatment was examined using a treatment evaluation questionnaire and qualitative interview. This trial has been registered on 3/10/2024 ( https://doi.org/10.1186/ISRCTN61068398 ) and is complete. Results Following treatment, participants (n = 13) reported significant decreases (with large effect sizes, r =.78 to 0.88) in the levels of anxious preoccupation in response to cancer, physical functioning, the non-judging facet of mindfulness, and a significant increase in perceived functional wellbeing. Qualitative analysis indicated that participants valued the social support element of the group format and for the intervention to be offered before and after the allogeneic HSCT procedure. Conclusions This study found that a tailored six-week mindfulness group intervention was feasible and accepted by haematological cancer patients post-HSCT and that participants reported improvements in factors such as functional wellbeing and reductions in anxious preoccupation.